State control of civil society organizations: the case of Turkey. Issue 2 (23rd February 2017) - Doyle, Jessica Leigh
ABSTRACT: Over the past few decades there has been a great deal of interest in the academic literature on the relationship between civil society organizations (CSOs) and the state, and the impact of state power on CSOs in the Middle East North Africa (MENA) region. Yet, despite this interest, very few detailed empirical explorations of these issues have been conducted to date. Of the detailed empirical work that does exist, none has focused on state–CSO relations in a democratic context in the MENA. This paper contributes to filling this gap by examining these relations and their implications in the Turkish context. More specifically, this paper explores the democratizing role of independent women's organizations in Turkey and the ways in which the state has sought to exert power over and control these organizations. The methodology consists of a series of 38 in-depth interviews with both registered and unregistered women's organizations from across the seven administrative regions of Turkey. The findings show that while CSOs do challenge the state in some regards, the state is by far the more powerful actor and very effective at moderating and de-radicalizing civil society. The state does this by controlling the areas in which CSOs can operate and be effective, and through the use of repressive measures. The results show that thease measures have the effect of tempering the demands of CSOs and reducing their capacity to challenge and counterbalance state power.